PENGARUH MIND MAPPING DENGAN MODEL PEMBELAJARAN SNOWBALL THROWING TERHADAP HASIL BELAJAR BIOLOGI PADA MATERI SISTEM GERAK DI SMA NEGERI 2 TARUNA BHAYANGKARA - Ferdiana, Ferdiana; Eka Puspita Kartika Sari; Riris Idiawati (Tadris IPA Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2025)
Improvements in student learning outcomes are highly dependent on the learning strategies used by teachers in the classroom. Conventional, teacher-centered learning methods often result in students being less active and having difficulty understanding the material, especially in biology, which contains many abstract concepts. One solution to overcome this is to combine mind mapping and the Snowball Throwing learning model. Mind mapping helps students summarize and organize information visually, thereby facilitating concept understanding. Meanwhile, Snowball Throwing encourages students to actively participate through question and answer sessions and enjoyable group discussions. The research method used was a quasi-experiment with a pretest-posttest control group design. The purpose of the study was to determine the effect of mind mapping with the Snowball Throwing learning model on biology learning outcomes in the movement system material at Taruna Bhayangkara 2 Public High School. Thus, it can be concluded that the use of mind mapping with the Snowball Throwing learning model has a positive and significant effect on students' biology learning outcomes in the movement system material.